Optimalisasi Sarana dan Prasarana Sekolah Menengah Kejuruan: Apa Faktor Penentunya? - Agustin Hanivia Cindy; Sugiyono Sugiyono; Husaini Usman (Lentera: Jurnal Ilmiah Kependidikan, 2023)
The research aims to know the factors that influence optimizing vocational high school facilities and infrastructure. By optimizing vocational high school facilities and infrastructure, it becomes strategic enough to contributeto the administrative performance, quality of learning, and quality of graduates. The research used a quantitative approach using questioners as the instruments of data collection with several 124 respondents.The analysis technique used a multiple regression test with one dependent variable and four independent variables. The results of the research conclude that the factors of student need (ρ = 0,016) and motivation (ρ = 0,024) significantly influence while the factor of rule (ρ = 0,169) and partnership (ρ = 0,108) do not significantly influence the optimization of facilities and infrastructures in Vocational High School.The four factors have a significant effect on ρ = 0,000.